Perceptions of Students Receiving the Scholarship for High-Achieving Students from Low-Income Families on Affiliate Marketing in the Community Education Study Program at Sriwijaya University - Sapitri, Sapitri; Saputra, Ardi (Journal of English Language and Education, 2025)
This study aims to determine the perception of Bidikmisi scholarship recipient students towards affiliate marketing in the Community Education Study Program, Sriwijaya University. The main focus of this study is how students view affiliate marketing as an alternative economic opportunity amidst socio-economic limitations and diverse educational backgrounds. This study uses a qualitative approach with a descriptive method. Data collection techniques are carried out through interviews, observations and documentation. The informants in this study were 6 students who came from Bidikmisi program recipient students. Based on the analysis and in this study, it can be concluded that from 3 indicators, namely social indicators of interest in affiliate marketing arise from the influence of the surrounding environment and social media, economic indicators, financial limitations are a driving factor for Bidikmisi students to seek alternative income, educational indicators, education is important to improve the ability to develop potential. The results of this study indicate that most Bidikmisi students have a positive perception of affiliate marketing as an opportunity to increase income without disrupting academic activities. However, there are also obstacles such as limited access to technology and lack of understanding of digital marketing.